Design Development of the JekNyong Application Using the Design Thinking Method - Pambudi, Wendri Tri; Wardhana, Ariq Cahya (Universitas Budi Darma, 2025)
The JekNyong application is a platform that allows the people of Banyumas Regency to sell household waste for recycling. However, the application’s user adoption rate remains low, with only 3.33% of families using it and a rating of 3.4 on the Google Play Store. This is due to an unintuitive interface design and limited feature accessibility. An initial usability test showed a task success rate of 75%, a time-based efficiency of 0.0206 goals/second, and a System Usability Scale (SUS) score of 63. The design development process followed the Design Thinking methodology through the stages of empathy, problem definition, ideation, prototyping, and testing. Several improvements were made to navigation, feature accessibility, and app layout. The second round of testing revealed significant improvements: the task success rate increased to 95.83%, time-based efficiency rose to 0.0382 goals/second, and the SUS score jumped to 86. These results indicate that the design improvements successfully enhanced the application's effectiveness and efficiency in accessing features.